Review on bug-report analysis techniques and approaches - Romanova, U. V.; Liutenko, Iryna Victorivna (Національний технічний університет "Харківський політехнічний інститут", 2022)
The paper presents a review on the existing works on bug-report analysis. In particular, this paper provides some background on bug-reports, describes main approaches to bug-report deduplication, prioritization and triage.
Keywords: bug-reports; bug-report analysis; bug-report deduplication; prioritization; triage; bug report processing; software; automated bug-report processing; software bugs; звіти про помилки; аналіз звітів про помилки; дедуплікація звітів про помилки; визначення пріоритетів; сортування; обробка звітів про помилки; програмне забезпечення; автоматизована обробка звітів про помилки; програмні помилки